Diagnostic challenges of giant cervical pilomatrixoma mimicking malignancy: case report and focused literature review - Urechescu, Horatiu; Pricop, Marius; Zara, Flavia; Closca, Raluca Maria; Streian, Felicia (Frontiers in Medicine, 2026)
Pilomatrixoma is a benign skin adnexal tumor arising from the hair-follicle matrix. While typically small and slowly growing, rare “giant” variants (>5 cm)—especially in the cervical region—may clinically and radiologically mimic malignant masses, posing a significant diagnostic challenge. We report a case of a 29-year-old male presenting with a solitary, firm, subcutaneous mass (~6 cm) in the left anterior cervical region, which enlarged rapidly over 6 months without pain or systemic symptoms. Contrast-enhanced CT revealed a well-defined, heterogeneous subcutaneous lesion without muscular or vascular invasion. Core needle biopsy (CNB) supported a diagnosis of pilomatrixoma. The mass was completely excised under IV sedation and local anesthesia. Histopathology confirmed classic pilomatrixoma features (basaloid cells, shadow cells, foreign-body giant cell reaction). At one-year follow-up the patient was disease-free, and scar outcome was excellent. This case underscores the importance of including giant pilomatrixoma in the differential diagnosis of large cervical soft-tissue masses. Histopathological examination remains essential for definitive diagnosis, while CNB can guide preoperative planning. Complete surgical excision yields excellent outcomes with minimal morbidity, avoiding overtreatment for suspected malignancy.